ANÁLISIS INTEGRAL DE ASPECTOS AMBIENTALES, DE PRODUCCIÓN Y DE SALUD OCUPACIONAL EN UNA EMPRESA PYMES - Caballero, Aldo L.; Dekun, Maria C.; Katogui, Sergio E.; Gladis G. G. C.; Kerkhoff, Alejandro J. (Salão do Conhecimento, 2013)
Resumo